2015
DOI: 10.1021/mp500520r
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin as Carrier and Adjuvant in Cocaine Vaccine Development

Abstract: Cocaine abuse is problematic, directly and indirectly impacting the lives of millions, and yet existing therapies are inadequate and usually ineffective. A cocaine vaccine would be a promising alternative therapeutic option, but efficacy is hampered by variable production of anticocaine antibodies. Thus, new tactics and strategies for boosting cocaine vaccine immunogenicity must be explored. Flagellin is a bacterial protein that stimulates the innate immune response via binding to extracellular Toll-like recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 81 publications
(79 reference statements)
2
51
0
Order By: Relevance
“…Their computational results agreed with those used for experimentation since then in a TLR5 reporter assay: the modiied lagellin protein still activated TLR5 when the hapten density was <10 GNE per FliC. Finally, the authors showed that cocaine-lagellin conjugates induced, in a dose-dependent model, the production of anticocaine antibodies in mice, improving the response with the adjuvant alum [73,74].…”
Section: Vaccines To Treat Addictionssupporting
confidence: 73%
See 2 more Smart Citations
“…Their computational results agreed with those used for experimentation since then in a TLR5 reporter assay: the modiied lagellin protein still activated TLR5 when the hapten density was <10 GNE per FliC. Finally, the authors showed that cocaine-lagellin conjugates induced, in a dose-dependent model, the production of anticocaine antibodies in mice, improving the response with the adjuvant alum [73,74].…”
Section: Vaccines To Treat Addictionssupporting
confidence: 73%
“…Again, bioinformatics was necessary to assess the secondary structure and MHC-II binding predictions for FliC and mFliC, employing the PSIPRED (htp://bioinf. cs.ucl.ac.uk/psipred/) method and the external software from IEDB (htp://www.immunoepitope.org/), respectively [74].…”
Section: Vaccines To Treat Addictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…11-12 In the field of vaccine development, new adjuvants are highly sought after that can stimulate a robust humoral immune response. 13-14 …”
Section: Introductionmentioning
confidence: 99%
“…99 A cocaine hapten conjugated to the TLR5 agonist flagellin elicited greater cocaine-specific Ab concentrations than the same hapten conjugated to KLH. 100 A novel nicotine vaccine employed a peptide-based trimeric coiled-coil (TCC) carrier containing CD4 C T cell epitopes.…”
Section: Pre-clinical Developmentmentioning
confidence: 99%